Tingkat Kepuasan Masyarakat Terhadap Pelayanan Di Sentra Pelayanan Kepolisian Terpadu (SPKT) Polres Tana Toraja - Pongtuluran, Althon K.; Mengga, Grace Sriati; Ronal, Marinus (UKI Toraja Press, 2021)
The formulation of the problem in this study is the level of community satisfaction with services at the Integrated Police Service Center (SPKT) Polres Tana Toraja. The problem in this study is how the level of community satisfaction with services in SPKT. The purpose of this study was to determine the level of community satisfaction with services at the SPKT Polres Tana Toraja. The technique of collecting data in this study was by conducting observations, interviews, and questionnaires with 50 respondents. The data analysis technique in this study is a quantitative descriptive method and the use of the Decree of the Minister of Administrative and Bureaucratic Reform No. 14 of 2017 concerning Guidelines for the preparation of community satisfaction surveys for service delivery units of government agencies. The results of this study are the level of community satisfaction with services at SPKT is in the good category with an IKM value of 80,834, because the value is between 76.61-88.30 which is in good service quality (B).